Epigenetic and microRNA regulation during osteoarthritis development - Chen, Di (F1000Res, 2015)
Osteoarthritis (OA) is a common degenerative joint disease, the pathological mechanism of which is currently unknown. Genetic alteration is one of the key contributing factors for OA pathology. Recent evidence suggests that epigenetic and microRNA regulation of critical genes may contribute to OA development. In this article, we review the epigenetic and microRNA regulations of genes related to OA development. Potential therapeutic strategies may be developed on the basis of novel findings.